2020
DOI: 10.1021/acs.jafc.9b06850
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomics of Milk Fat Globule Membrane in Human Colostrum and Mature Milk: New Insights into Changes in Protein Phosphorylation during Lactation

Abstract: Phosphorylation is a widespread posttranslational protein modification and is important in various biological processes. However, milk fat globule membrane (MFGM) phosphoproteins have not been explored systematically in human milk. Here, we used quantitative phosphoproteomics to analyze phosphorylation sites in human MFGM proteins and their differences at different stages of lactation; 305 phosphorylation sites on 170 proteins and 269 phosphorylation sites on 170 proteins were identified in colostrum and matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 47 publications
(83 reference statements)
1
39
0
Order By: Relevance
“…The most shared proteins across species were involved in protein/vesicle-mediated transport, along with major MFGM proteins such as BTN, ADPH, FABP, and MUC1. The main difference regarding human MFGM proteome was a higher enrichment in enzymes involved in lipid catabolism, also reported in Liao et al [ 68 ] and in a set of immune response proteins [ 61 , 72 ].…”
Section: Comparison Of Mfgm Proteome Between Different Species Andmentioning
confidence: 73%
See 4 more Smart Citations
“…The most shared proteins across species were involved in protein/vesicle-mediated transport, along with major MFGM proteins such as BTN, ADPH, FABP, and MUC1. The main difference regarding human MFGM proteome was a higher enrichment in enzymes involved in lipid catabolism, also reported in Liao et al [ 68 ] and in a set of immune response proteins [ 61 , 72 ].…”
Section: Comparison Of Mfgm Proteome Between Different Species Andmentioning
confidence: 73%
“…These 48 phosphoproteins were mainly associated with immune-related processes. The results showed that there were more immune system process-related phosphoproteins in human colostrum MFGM than in mature MFGM, probably because of the important role that colostrum has in building the immune system of newborns [72].…”
Section: Comparison Of Mfgm Proteome Between Different Species and Lamentioning
confidence: 95%
See 3 more Smart Citations